Nitroxidized-Albumin Advanced Glycation End Product and Rheumatoid Arthritis - Akhlas TARANNUM; Zarina ARIF; Khursheed ALAM; Shafeeque AHMAD; Moin UDDIN (Archives of Rheumatology, 2019)
Rheumatoid arthritis (RA) is an autoimmune disease whose major clinical consequence is inflammation of small joints and contiguous structures. Oxidative and nitrosative stress along with increased formation of advanced glycation end products (AGEs) play an important role in the disease process. Generation of reactive species during glycation of proteins further adds to the oxidative and nitrosative stress. Albumin, being the most abundant plasma protein, is frequently targeted by different oxidizing and nitrating agents, including peroxynitrite (OONO-) anion. Albumin is also targeted and modified by dicarbonyl metabolites (glyoxal and methylglyoxal) which are formed in oxidative and non-oxidative processes during the synthesis of AGEs. The endogenously formed OONO- and dicarbonyls may modify plasma albumin including those albumin that have travelled or migrated to synovial cells and caused nitration, oxidation, and glycation. These modifications may produce crosslinks, aggregate in albumin and confer immunogenicity. Simultaneous modification of albumin by OONO- and dicarbonyls may generate nitroxidized-AGE-albumin which may persist in circulation for a longer duration compared to native albumin. Nitroxidized-AGE-albumin level (or serum autoantibodies against nitroxidized- AGE-albumin) along with other pre-clinical features may help predict the likely onset of RA.